Suture-Mediated Patent Fossa Ovalis Closure - Achille Gaspardone, MD, MPhil; Gregory A. Sgueglia, MD, PhD; Antonella De Santis, MD; Fabiana Piccioni, MD; Emanuela D’Ascoli, MD; Tommasa Siragusa, RCIS; Maria Iamele, MD; Maria Benedetta Giannico, MD; Fabrizio D’Errico, MD; Carlo Gaspardone, MD (JACC: Advances, 2025)
Background: At short-term follow-up, percutaneous suture-mediated patent fossa ovalis (PFO) closure appears as a safe and effective alternative to device-based methods. This study represents the largest cohort of patients undergoing suture-mediated PFO closure with the longest follow-up reported to date. Objectives: The aim of the study was to assess the long-term clinical safety and efficacy of suture-mediated PFO closure and identify predictors of technical success. Methods: Between 2016 and 2023, 703 consecutive patients (age 47 ± 12 years, 62% women) with PFO-associated stroke or transient ischemic attack underwent suture-mediated PFO closure. All patients were followed up using transthoracic echocardiography with a bubble test for 12 months to detect significant residual shunt (>1 grade on a 0-3 scale) and clinically for 4 years. Results: At a median clinical follow-up of 4 years, no recurrent cerebrovascular events (stroke or transient ischemic attack) were reported, and only 1 transient episode of atrial fibrillation occurred. Among the 703 patients, 91 showed residual shunt during follow-up (median transthoracic echocardiography follow-up time of 11.5 months). Multivariable analysis identified independent predictors of significant residual shunt: PFO maximum width (OR per 1 mm increase: 1.34; 95% CI: 1.19-1.50; P < 0.001), minimum PFO length (OR per 1 mm increase: 0.92; 95% CI: 0.86-0.98, P = 0.015), atrial septal aneurysm (OR: 1.83; 95% CI: 1.14-2.91; P = 0.011), and grade 3 Valsalva shunt (OR: 2.19; 95% CI: 1.25-3.90; P < 0.007). A scoring system was developed based on the independent predictors of residual right-to-left shunt ≥2, assigning points according to the magnitude of the logistic regression coefficients. Based on these variables, the Length, Aneurysm, Severe Shunt, Opening (LASSO) score was developed and internally validated (area under the curve: 0.73; 95% CI: 0.68-0.78). Conclusions: Suture-mediated PFO closure demonstrates long-term safety and efficacy. The LASSO score is a valuable tool for optimizing patient selection for this procedure.